High-temperature metamorphic garnets from Grenvillian granulites of southwestern Oaxacan Complex (Southern Mexico): petrology, geochemistry, geothermobarometry, and tectonic implications - Culí, Laura (2022)
The basement of eastern Mexico comprises Grenvillian-age granulite-facies metamorphic rocks. The Oaxacan Complex represents the largest outcrop belt of this basement in Mexico. In this work, southwestern Oaxacan Complex garnets are studied from a petrographical, geochemical, and geothermobarometrical perspective for the first time. The studied garnets display different grain sizes nucleated in a polyphase evolution. The almandine end member proportion is similar in all of the studied lithotypes. The highest pyrope concentrations are found in Qz Fsp paragenesis and ultramafic rocks and the lowest pyrope concentrations are found in amphibolite. The highest grossular and spessartine concentrations are found in the amphibolite lithotype. Southwestern Oaxacan Complex garnets from paraderivate samples are more enriched in Rb, Ba, Pb, Ni, and Zn than those from orthoderivate samples enriched in Ti and V. This fact is related to the nature of the protoliths and the mineral phases that fractionate the same minor and trace elements. Garnets from para-and orthoderivate samples display 0.02–1.1 Eu/Eu* anomalies. This fact indicates that almost all of the garnets formed while the plagioclase was stable, and it does not rule out the interpretation that some garnets were peritectic. The pressure obtained using a Grt-Opx-Pl-Qz geobarometer in the southwestern Oaxacan Complex is higher than the pressure obtained in the northern part of the Complex, and it is consistent with the pressure obtained in the Grenvillian-age granulites of the Novillo Gneiss from northeastern Mexico. Geothermobarometric studies reveal different P-T features at the study site, so different structural levels of the orogen are inferred.